THE WOND IN THE CLUTCES OF TOTALITARISM: DEWOTED TO THE HISTORI OF PRESS AND PUBLISHING IN KOLOMYIA (LATE 1930S – LATE 1980S) - Vasylchuk, M. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The peculiarities of printing development, newspaper and publishing businen in Kolomyia (Ivano-Frankivsk region) are considered in the text. It envolves the period of late 1930s till late 1980s. The attention ir paid to historic-printing knowledge aspect of the problem and the oblectiwe picture of the publisching process as a complete phenomenon with its peculiarities, positive and negative moments are reconstructed, the complex way of searching of national orientation in the conditions of total political vegime is shown.